Comparison of three continuous positive airway pressure (CPAP) interfaces in healthy Beagle dogs during medetomidine–propofol constant rate infusions. (March 2018) - Meira, Carolina; Joerger, Fabiola B.; Kutter, Annette P.N.; Waldmann, Andreas; Ringer, Simone K.; Böehm, Stephan H.; Iff, Samuel; Mosing, Martina
Abstract: Objective: To compare the efficacy of three continuous positive airway pressure (CPAP) interfaces in dogs on gas exchange, lung volumes, amount of leak during CPAP and rebreathing in case of equipment failure or disconnection. Study design: Randomized, prospective, crossover, experimental trial. Animals: Ten purpose-bred Beagle dogs. Methods: Dogs were in dorsal recumbency during medetomidine–propofol constant rate infusions, breathing room air. Three interfaces were tested in each dog in a consecutive random order: custom-made mask (M), conical face mask (FM) and helmet (H). End-expiratory lung impedance (EELI) measured by electrical impedance tomography was assessed with no interface (baseline), with the interface only (No-CPAP for 3 minutes) and at 15 minutes of 7 cmH2 O CPAP (CPAP-delivery). PaO2 was assessed at No-CPAP and CPAP-delivery, partial pressure of inspired carbon dioxide (PICO2 ; rebreathing assessment) at No-CPAP and the interface leak (ΔPleak ) at CPAP-delivery. Mixed-effects linear regression models were used for statistical analysis ( p  < 0.05). Results: During CPAP-delivery, all interfaces increased EELI by 7% ( p  < 0.001). Higher ΔPleak was observed with M and H (9 cmH2 O) in comparison with FM (1 cmH2 O) ( p  < 0.001). At No-CPAP, less rebreathing occurred with M (0.5 kPa, 4 mmHg) than with FM (1.8 kPa, 14 mmHg) and with H (1.4 kPa, 11 mmHg), but also lower PaO2 was measured with M (9.3 kPa, 70 mmHg) than with H (11.9 kPa, 90 mmHg) and FM (10.8 kPa, 81 mmHg). Conclusions and clinical relevance: All three interfaces can be used to provide adequate CPAP in dogs. The leak during CPAP-delivery and the risk of rebreathing and hypoxaemia, when CPAP is not maintained, can be significant. Therefore, animals should always be supervised during administration of CPAP with any of the three interfaces. The performance of the custom-made M was not superior to the other interfaces.